Evaluation of a Novel Method of Teaching Endobronchial Ultrasound: Physician- Versus Respiratory Therapist-Proctored Simulation Training. Issue 4 (2013) - Stather, David Ryan; Chee, Alex; MacEachern, Paul; Dumoulin, Elaine; Hergott, Christopher A; Gelberg, Jacob; Scott, Sandra D; De Guzman, Sylvia; Tremblay, Alain
Abstract : BACKGROUND: Computer endobronchial ultrasound (EBUS) simulators have been demonstrated to improve trainee procedural skills before attempting to perform EBUS procedures on patients. OBJECTIVE: To compare EBUS performance following training with computer simulation proctored by EBUS-trained respiratory therapists versus the same simulation training proctored by an interventional respirologist. METHODS: The present analysis was a prospective study of respiratory medicine trainees learning EBUS. Two cohorts of trainees were evaluated using a previously validated method using simulated cases with performance metrics measured by the simulator. Group 1 underwent EBUS training by performing 15 procedures on an EBUS simulator (n=4) proctored by an interventional respirologist. Group 2 received identical training proctored by a respiratory therapist with special training in EBUS (n=10). RESULTS: No significant differences between group 1 and group 2 were apparent for the primary outcome measures of total procedure time (15.15±1.34 min versus 14.78±2.88 min; P=0.816), the percentage of lymph nodes successfully identified (88.8±5.4 versus 80.91±8.9; P=0.092) or the percentage of successful biopsies (100.0±0.0 versus 98.75±3.95; P=0.549). The learning curves were similar between groups, and did not show an obvious plateau after 19 simulated procedures in either group. DISCUSSION: Acquisition of basic EBUS technical skills can be achieved using computer EBUS simulation proctored by specially trained respiratory therapists or by an interventional respirologist. There appeared to be no significant advantage to having an interventional respirologist proctor the computer EBUS simulation.